Coping strategies and psychological defense mechanisms of the person to overcome burnout in the attorneyscommunity - Eduard Krainikov; Konstantin Pilkov (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article presents the results of empirical study on the relationship between the dominant coping strategies and psychological defense mechanisms that are used by lawyers with the syndrome of emotional burnout. Attorneys with the existing syndrome of burnout demonstrate a very high level of aggressive humor as a kind of psychological defense mechanism. The analysis revealed that emotional burnout due to the lack in the arsenal of an individual's adaptive coping strategies and the overall intensity of psychological defense mechanisms as well as the fact that the manifestations of aggressive and self- deprecating humor of the individual combined with weak adaptive coping model of entry into social contact.
Keywords: coping strategies; psychological defense mechanisms; emotional burnout; lawyer environment